Challenges and Steps in Living Quran and Hadith Research: An Introduction - Engkizar, Engkizar; Jaafar, Azhar; Masuwd, Mowafg Abrahem; Rahman, Ikhwan; Datres, Datres; Taufan, Muhammad; Akmal, Fauzi; Dasrizal, Dasrizal; Oktavia, Gifa; Yusrial, Yusrial; Febriani, Afifah (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
The theme of living Quran and Hadith research is actually not familiar among Islamic academics, especially students, even among lecturers of Islamic universities in Indonesia. In general, it can be stated that living Quran and Hadith research is a research approach that studies how the concept, practice or the occurrence of errors in the implementation of the values of the Quran and Hadith in the midst of the lives of Muslim communities that need to be maintained the purity of its teachings, while for those who are mistaken there needs to be improvement both in concept and practice. Precisely, this article aims to analyze what are the opportunities for living Quran and Hadith research in the context of future research and how the steps should be taken if a researcher wants to conduct living Quran and Hadith research. The research was carried out using qualitative methods with a phenomenological approach and content analysis, data sources were taken through in-depth interviews with six selected informants and experts in the field of Quran and Hadith, further data sources were taken from the opinions and findings of previous researchers who had been written in the form of books or scientific articles and had been published in both national and international journals. The findings found that, first, living Quran and Hadith research has opportunities and will make a real contribution to the development of theory, Islamic science and Muslim society, because the Quran and Hadith are the main sources of Muslims in living life, of course this issue and topic will always be interesting and dynamic. In addition, living Quran and Hadith research will always be a concern of Muslim and non-Muslim academics both in terms of issues, practices because it gives birth to the latest findings from various analyzes and perspectives. second, there are five processes or steps that a researcher must take to carry out living Quran and Hadith research. These findings can be used as motivation for researchers to be actively involved in living Quran and Hadith research, as well as guidance for researchers who are interested in conducting living Quran and Hadith research.